The Revitalization of Malay Sultanate Culture Arts through Mapping as an Asset for Tourism Development in North Sumatra - Yusnizar Heniwaty; Muhammad Anggi Daulay; Ika Purnamasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Art and cultural products in Deli Serdang Regency, Batubara Regency, and Tanjung Balai City are inseparable from the Malay kingdom sites that were established at the time. The Malay kingdom was led by the sultan, usually marked by the establishment of the palace as a sign of the grandeur and sovereignty of the king and all his relatives, which then made the palace a place to live, consult, and decide on an event. In addition to the splendor of the palace, various arts and cultural products that became symbols of local wisdom became part of his time, but nowadays various art and cultural products are considered to have no maximum implementation and distribution to the younger generation as holders of cultural relay batons. So that these products are not extinct, they need the attention of the entire community, government, and stakeholders. One way to bring it back is to revitalize it by developing it into a tourist dish. This study aims to: Know the condition of art and culture, cultural potential, in the three regions of the Malay sultanate, and the efforts of the government, artists in revitalizing the potential of art and culture. The research method used is descriptive qualitative, with data collection in the form of, mapping, interviews, and observations. The results of the study explained that each of Serdang, Batubara, and Tanjungbalai Sultanates had potentials that could characterize their regions, there were: Serdang Sultanate with Makyong arts, Tanjungbalai Sultanate with Gubang arts, and Batubara Sultanate had the story and Lima Laras palace. These three potentials can be developed into cultural tourism attractions in the region and North Sumatra. This requires the creativity of artists in developing them from every aspect. Government intervention also becomes necessary in sustaining the existence of cultural arts by making policies that sustain the art and culture. In addition, for the cultural actors can develop professionalism in accordance with their field of expertise.